Politeness Strategies in Language Use among Generation Alpha in the Interactions of Ryu Kintaro Little Sultan - Yulisa Aulia; Amelia Nur Azizah; Tatu Siti Rohbiah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Some people experience subjective complaints such as redness, itching, burning, or a sensation of heat in their eyes, which can be linked to the use of digital technology. This has led to a shift in human communication, where traditional face-to-face interactions are increasingly taking place in virtual spaces that are fast-paced and ever-changing, such as YouTube. This change doesn't just affect technical aspects, but also rebuilds the user's language identity, where language now serves as a strategic tool to build social connections and maintain a positive self-image. This study aims to examine the politeness mechanisms used by Ryu Kintaro in his interview video on the YouTube channel Tom MC Ifle, using the theory framework of Brown and Levinson and the principles of politeness from Leech. Subjective complaints may include symptoms such as red eyes, itching, burning, and a hot sensation. Pragmatics is a branch of linguistics that studies the conditions for the appropriate use of language in the communication process, which is very closely tied to the external context of language. The method used was a descriptive qualitative approach, involving the analysis of 28 speech data collected through the techniques of listening and recording. The research results show that positive politeness strategies were used in 64.3% of the interactions. This shows that the subject tends to use strategies such as sharing personal experiences, providing reasons, and building optimism to reduce face-threatening situations while also strengthening cooperation among communicators. This finding shows that politeness among Generation Alpha hasn't disappeared despite the stigma around digital slang language. Instead, it has changed its function to remain relevant, responsive, and adaptable in today's digital communication environment, helping to keep social relationships in harmony.